The Influence The Influence Of Brand Ambassador Jennifer Coppen And Influencer Marketing On The Purchase Decision Of Facetology Skincare Products In Gen Z Consumers - Vivi Puspitasari Wamer; Fedianty Augustinah; Andry Herawati; Sarwani (Cita konsultindo, 2025)
The main focus of this study is directed to uncover the understanding of the influence of Brand Ambassador Jennifer Coppen and Influencer Marketing on the Purchase Decision of Facetology skincare products in Generation Z consumers. user. This research was carried out using a quantitative pattern based on descriptive tendencies and oriented towards cause-effect relationships. A sample of 96 respondents from Gen Z was obtained through non-probability sampling techniques and collected through an online questionnaire. Testing of the validity and internal stability of the instrument was carried out, then the results obtained were used as the basis for multiple linear regression exploration using the SPSS vehicle. The results of the data exploration imply that the Brand Ambassador and Influencer Marketing variables make a significant positive contribution to the formulation of purchase decisions, both individually and simultaneously. The determination coefficient (R²) recorded at 0.710 indicates that 71% of the dynamics of purchasing decisions can be reconstructed from the fluctuations of the two independent variables. Between the two, Influencer Marketing occupies the dominant position in terms of influence. These findings reaffirm the relevance of a planned, segmentation-based digital promotion strategy to reach Gen Z—a generation known for being responsive to technological innovation as well as social media-based content consumption.